Drying of almonds II: multiple particles - Chilka, A. G. (Indian Chemical Engineer, 2017)
Computational modelling is an efficient and effective tool for modelling the drying process for food products. Developing validated computational models for drying processes is essential to build energy-efficient drying units, producing uniform quality of dried products. This work presents drying behaviour of almonds with a specific focus on understanding interaction among multiple almonds. Eight (2 × 2 × 2) particles and twenty seven (3 × 3 × 3) particles arranged in the shape of a cuboid were used to conduct drying experiments in a Mettler Toledo Moisture Analyzer unit. Experiments were conducted to measure the moisture loss data with respect to drying time using almond kernels. Experimental data were used to understand drying kinetics as well as variation in moisture content with respect to their positions in a cuboid. Computational fluid dynamics based simulations were carried out for the flow, heat transfer and drying of particles in the unit. Actual geometry of individual particles was considered in simulations to predict the variation in velocity, heat and mass transfer coefficients for all the particles. Simulations predicted moisture loss data that matches well with the experimentally measured values. Average moisture for each layer was also compared for various intermediate drying times. Simulation results captured the overall drying process for multiple particles system adequately. The results are compared with the results obtained with drying of a single almond. The approach, models and presented results will be useful for designing large-scale drying units for almonds. © 2017 Indian Institute of Chemical Engineers
Keywords: Almonds; CFD; Drying